Collocations of verb + time in English and verb + waktu in Indonesian: A Corpus-Driven Study of Time Metaphors - Icuk Prayogi; Tri Mastoyo Jati Kesuma; Daru Winarti (Universitas Ahmad Dahlan, 2022)
Time is one of the salient concepts in human life since we live and act in time. Thus, research investigating time is always intriguing yet perplexing. This study aims to describe the collocations of verbs with the most frequent lexical item for temporal concept, i.e., time. The present study also compared the collocations to those in Indonesian counterparts, that is verb + waktu. This is a corpus-driven study using two reference corpora, Corpus of Contemporary American English for English data, and Leipzig Corpus Collection for Indonesian data. The association measure used to identify the verb collocates is Mutual Information (MI) and the results of collocates in both languages were compared. The result of the study shows that there are 15 most frequent verb collocates of time and waktu for both English and Indonesian, e.g., have, spend, take, membutuhkan, memanfaatkan, memerlukan, etc. Of all these collocates, there are some similarities and differences that can be mapped. The similarities are associated with basic mappings of time metaphor, e.g., TIME IS MONEY, TIME IS A RESOURCE, TIME IS A COMMODITY, and TIME IS MOTION. Despite the similarity, some differences are also identified which might be affected by limited number of verb collocates analyzed in the present study (e.g., TIME IS A FLEXIBLE OBJECT, TIME IS A CONTAINER, TIME IS A BEING, TIME IS A VICTIM). The results of the study can be used as a reference for teachers in teaching or designing teaching materials on time expressions or time metaphor.